A culture of conspiracy: apocalyptic visions in contemporary America - Barkun, Michael (Comparative studies in religion and society, 2003)
The nature of conspiracy belief -- Millennialism, conspiracy, and stigmatized knowledge -- New world order conspiracies (I) : the new world order and the illuminati -- New world order conspiracies (II) : a world of black helicopters -- UFO conspiracy theories, 1975-1990 -- UFOs meet the new world order : Jim Keith and David Icke -- Armageddon below -- UFOs and the search for scapegoats (I) : anti-Catholicism and anti-Masonry -- UFOs and the search for scapegoats (II) : anti-Semitism among the aliens -- September 11th : the aftermath